2022
DOI: 10.3390/jcm11113091
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of New Bioactive Materials on Pulp–Dentin Complex Regeneration in the Assessment of Cone Bone Computed Tomography (CBCT) and Computed Micro-Tomography (Micro-CT) from a Present and Future Perspective—A Systematic Review

Abstract: The present paper is the first article providing a systematic literature review on the visualization of tertiary dentin influenced by modern bioactive materials in CBCT and micro-CT. Six database searches of studies on tertiary dentin visualization using CBCT produced 622 records in total, and the search of the studies on tertiary dentin using micro-CT produced 502 records in total. The results were thoroughly selected considering the inclusion criteria, and five research papers using CBCT and nine research pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(216 reference statements)
0
4
0
Order By: Relevance
“…All CBCT measurement was performed by an expert radiologist who was blinded to study groups. The obtained data were tabulated in millimeter (mm) (2,14). using a Microsoft Word Excel sheet and relevant statistical tests were implemented.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All CBCT measurement was performed by an expert radiologist who was blinded to study groups. The obtained data were tabulated in millimeter (mm) (2,14). using a Microsoft Word Excel sheet and relevant statistical tests were implemented.…”
Section: Radiographic Assessmentmentioning
confidence: 99%
“…voltage: 20.0 kV) (Figure 2, a). Obtained EDX elemental eggshell powder analysis revealed presence of calcium (51.55 wt %), aluminum (0.39 wt %), magnesium (0.60 wt %), oxygen (41.07 wt %), fluoride (0.00 wt %), and carbon (6.38 wt %) (Full scale counts: 15764, integral counts: 360812), (Figure 2, b) (13,14) .…”
Section: Characterization Of Eggshell Powdermentioning
confidence: 99%
“…CBCT is an innovative 3D imaging modality that provides a non-invasive option to evaluate dental tissues without the superimposition of surrounding structures [Scarfe and Farman, 2008]. In addition, CBCT was found to be more valid and reliable in measuring remaining dentin thickness in deep carious lesions and tertiary dentin thickness than traditional periapical X-rays when compared to histologic assessments [Kamal et al, 2021;Palczewska-Komsa et al, 2022;Sarhan et al, 2022]. Other studies have also shown that CBCT is the imaging modality of choice to evaluate secondary dentin formation in vivo [Tardivo et al, 2011;Ge et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, implantoprosthetic orthodontics and other fields of dentistry are experiencing rapid progression [1][2][3][4][5]. These implants use dental models created based on a matrix of impressions [6] and are produced when it is necessary to use braces to correct malocclusion, insert implants, crowns, or bridges.…”
Section: Introductionmentioning
confidence: 99%